High motivation for exercise is associated with altered chromatin regulators of monoamine receptor gene expression in the striatum of selectively bred mice. (7th November 2016) - Saul, M. C.; Majdak, P.; Perez, S.; Reilly, M.; Garland, T.; Rhodes, J. S.
Abstract : Although exercise is critical for health, many lack the motivation to exercise, and it is unclear how motivation might be increased. To uncover the molecular underpinnings of increased motivation for exercise, we analyzed the transcriptome of the striatum in four mouse lines selectively bred for high voluntary wheel running and four non‐selected control lines. The striatum was dissected and RNA was extracted and sequenced from four individuals of each line. We found multiple genes and gene systems with strong relationships to both selection and running history over the previous 6 days. Among these genes were Htr1b, a serotonin receptor subunit and Slc38a2, a marker for both glutamatergic and γ‐aminobutyric acid (GABA)‐ergic signaling. System analysis of the raw results found enrichment of transcriptional regulation and kinase genes. Further, we identified a splice variant affecting the Wnt‐related Golgi signaling gene Tmed5 . Using coexpression network analysis, we found a cluster of interrelated coexpression modules with relationships to running behavior. From these modules, we built a network correlated with running that predicts a mechanistic relationship between transcriptional regulation by nucleosome structure and Htr1b expression. The Library of Integrated Network‐Based Cellular Signatures identified the protein kinase C δ inhibitor, rottlerin, the tyrosine kinase inhibitor, Linifanib and the delta‐opioid receptor antagonist 7‐benzylidenenaltrexone as potential compounds for increasing the motivation to run. Taken together, our findings support a neurobiological framework of exercise motivation where chromatin state leads to differences in dopamine signaling through modulation of both the primary neurotransmitters glutamate and GABA, and by neuromodulators such as serotonin. Abstract : Figure 5C: Reciprocal relationships between the chromatin remodeling factor Baz1a, a histone H1 subunit H1f0, and a metabotropic serotonin receptor Htr1b is associated with high motivation for running.